Impact of Preoperative Clopidogrel Administration on Perioperative Blood Loss and Transfusion Requirements in Patients Undergoing Coronary Artery Bypass Graft Surgery - Keyvan Bagheri; Seyed Mohammad Reza Safavi; Azim Honarmand; Mohammadali Attari; Masoud Nazem; Javad Ahmadi; Mehdi Khazaei (مجله دانشکده پزشکی اصفهان, 2014)
Background: Clopidogrel is an adenosine-5' diphosphate (ADP) receptor antagonist that eventually inhibits platelet aggregation. It is used concomitantly with percutaneous coronary interventions and in patients with acute coronary diseases. This study was conducted to determine the effects of preoperative clopidogrel administration on perioperative blood loss and transfusion requirements in patients undergoing coronary artery bypass graft (CABG) surgery.